From tameness to wariness: chemical recognition of snake predators by lizards in a Mediterranean island - Mencía, Abraham; Ortega, Zaida; Pérez-Mellado, Valentín (PeerJ, 2017)
Antipredatory defenses are maintained when benefit exceeds cost. A weak predation pressure may lead insular lizards to tameness. Podarcis lilfordi exhibits a high degree of insular tameness, which may explain its extinction from the main island of Menorca when humans introduced predators. There are three species of lizards in Menorca: the native P. lilfordi, only on the surrounding islets, and two introduced lizards in the main island, Scelarcis perspicillata and Podarcis siculus. In addition, there are three species of snakes, all introduced: one non-saurophagous (Natrix maura), one potentially non-saurophagous (Rhinechis scalaris) and one saurophagous (Macroprotodon mauritanicus). We studied the reaction to snake chemical cues in five populations: (1) P. lilfordi of Colom, (2) P. lilfordi of Aire, (3) P. lilfordi of Binicodrell, (4) S. perspicillata, and (5) P. siculus, ordered by increasing level of predation pressure. The three snakes are present in the main island, while only R. scalaris is present in Colom islet, Aire and Binicodrell being snake-free islets. We aimed to assess the relationship between predation pressure and the degree of insular tameness regarding scent recognition. We hypothesized that P. lilfordi should show the highest degree of tameness, S. perspicillata should show intermediate responses, and P. siculus should show the highest wariness. Results are clear: neither P. lilfordi nor S. perspicillata recognize any of the snakes, while P. siculus recognizes the scent of M. mauritanicus and reacts to it with typical well-defined antipredatory behaviours as tail waving and slow motion. These results rise questions about the loss of chemical recognition of predators during island tameness and its related costs and benefits for lizards of insular habitats. In addition, this highlights the necessity for strong conservation measures to avoid the introduction of alien predators.
Keywords: Insular tameness; Antipredatory behaviour; Islands; Behavioural adaptations; Biological invasions; Lizards; Snakes; Chemoreception; Chemical cues; Mediterranean islands